Number One Reef: An overstepped segmented lagoon complex on the KwaZulu-Natal continental shelf - Andrew Green; Rio Leuci; Zane Thackeray; Godfrey Vella (South African Journal of Science)
This study of the bathymetry of the mid-shelf of the Durban Bight, KwaZulu-Natal revealed a series of previously undocumented seafloor features. These features were mapped using a high-resolution multibeam bathymetric echosounder and a detailed map of the seafloor topography was produced. We recognised several features that closely resemble features of contemporary segmented lagoon and lake systems: semicircular seafloor depressions, arcuate ridges, cuspate spits and prograding submerged barriers. Based on the striking similarity in morphology to Kosi Bay - a segmented lagoon system from the sandy northern KwaZulu-Natal coastal plain - a similar evolutionary model is proposed. This model is of an incised valley formed following a sea level lowering to the Last Glacial Maximum at about 18 000 BP. Thereafter, continued transgressive infilling occurred to a point where an extensive lagoon and back-barrier system was established. At this point, sea levels remained static, causing the net segmentation of the system and the slow closure of the tidal basins or circular depressions. This type of seafloor topography is rarely preserved and is the result of fortuitous cementation after deposition and the later removal of sediment that would ordinarily bury such features.